Advancing Diagnostics: The Role of Ultrasound and MR Imaging in Evaluating Musculotendinous Pathologies of the Shoulder Joint – A Comprehensive Literature Review - Alanai, Taflah Obeed; Almutairi, Meshari Thamer; Alshalawi, Sultan Obaid; Aladyani, Mohammed Fawaz Saed; Alrokhemi, Ahmad Solaiman; Al-Otaibi, Abdul Majeed Mansour; Almutairi, Nawaf Farhan; Alqahtani, Sarah Fahad Saad; Alsubaie, Fawaz Mufarrij Majed; Almutairi, Hamed Bader M (Journal of Ecohumanism, 2024)
Musculotendinous pathologies of the shoulder joint are a common source of pain and functional impairment, often requiring precise imaging for accurate diagnosis and management. This review explores the roles of ultrasound (US) and magnetic resonance imaging (MRI) in evaluating these conditions, focusing on their diagnostic strengths, limitations, and clinical applications. Ultrasound offers dynamic, real-time assessment with high accuracy for superficial structures, making it a cost-effective option for evaluating rotator cuff tears and tendinopathies. MRI, on the other hand, is the gold standard for comprehensive imaging of deep soft tissues, labral injuries, and subtle intra-articular abnormalities. Recent advances in both modalities, including AI-powered ultrasound and faster MRI sequences, have enhanced diagnostic capabilities. This review synthesizes evidence from the past decade, comparing the sensitivity, specificity, and cost-effectiveness of US and MRI while discussing scenarios where their integration can provide the most benefit. The findings emphasize the need for modality selection tailored to clinical presentations, the expertise of practitioners, and healthcare resource availability. Future research should aim to standardize imaging protocols and explore innovative multimodal approaches to improve diagnostic accuracy further.